The chaos theory of careers : a new perspective on working in the twenty-first century - Pryor, Robert; Bright, Jim (Routledge, 2011)
Outlines the application of chaos theory to the field of career development. This book represents a new perspective on the nature of career development. It emphasizes the dimensions of careers frequently neglected by accounts of careers such as the challenges and opportunities of uncertainty and the potential for information overload